TRANSLATION STRATEGIES OF PROPER NAMES IN JO’S BOYS AND HOW THEY TURNED OUT AND ITS INDONESIAN TRANSLATION - Wulandari, Ratna; Firstiyanti, Aulia; Sentana , Aswarini (Jurnal Ilmiah Multidisiplin, 2024)
The aim of this paper is to identify translation strategies applied by the translator in transferring an English children book to Indonesian. Proper names have a cultural connotation and should be translated using appropriate techniques whether they relate to people, locations, or other fictional characters, they usually have important language or cultural quirks that make translation challenging. The examination is carried out on the case of the translation of English novel entitled Jo’s Boys and How They Turned Out which written by Louisa May Alcott in 1886 and its translation entitled Jo’s Boys - Sepuluh Tahun Kemudian, translated by Djokolelono. The paper analyzes how proper names alluding to living animals, topographical or geological names were interpreted. The writer uses a qualitative descriptive method and will analyzed descriptively in the form of documents. The writer is comparing the proper name translation in source text and target text, and then categorize them into types of the proper name using theory from Anastasia Parianou (2007). Then, those categories are described and classified using theoy from Eirlys E. Davies (2003) to detect what translation strategies used by the translator. The result shows that from 189 data collected, there are 7 categories of proper names and 7 translation strategies detected. They are Personal names and personifications (65%), Geographical names (16%), Names of unique events (7%), Names of unique objects and works of art (6%), Names of institutions and facilities (4%), and Trademark names (2%). The translation strategies used by the translator are Preservation (93%), Localization (45%), Addition (33%), Transformation (9%), Creation (5%), Globalization (2%), and Omission (2%).